Development E-Catalogue Portfolio Design Architecture with Android Mobile Apps using Kodular Framework - yahfizham, Yahfizham; Sinaga, Imam Adlin (ULTIMA InfoSys, 2024)
The Bisma Kasada (Commanditaire Vennootschap/CV) is a company that provides technical consulting services to communities and governments. The Bisma Kasada covers various aspects of the field of work with minimal qualifications, including the process of promoting consultant services aspecially in the field of architecture. The Bisma Kasada continues to operate conventionally, with architects creating design portfolios of 2-dimensional and 3-dimensional architectural drawings of buildings or spatial layouts. Then, architects promote or market the portfolio to the public through printed brochures and social media. Using this method still presents several challenges, including the time, costs, and energy required for promotional activities, the challenge of updating product data, and the limited scope of promotion and marketing in the surrounding environment. The goal of this research is to develop an Android mobile-based E-Catalogue application, which can serve as a promotional and marketing tool for architectural design of the portfolios. The application, designed by the Bisma Kasada, incorporates a feature for cost estimation and calculation. In building the application, the author used the waterfall method, which consists of analysis stages, design stages, coding stages, and testing stages. We build the application based on android platform using the Kodular framework and Airtable database to strongly interfaced but simplify in the system.